Capture of mammal excreta by Nepenthes is an effective heterotrophic nutrition strategy. (28th October 2022) - Cross, Adam T; van der Ent, Antony; Wickmann, Miriam; Skates, Laura M; Sumail, Sukaibin; Gebauer, Gerhard; Robinson, Alastair
Abstract: Background and aims: While isotopic enrichment of nitrogen ( 15 N) and carbon ( 13 C) is often used to determine whether carnivorous plant species capture and assimilate nutrients from supplemental sources such as invertebrate prey or mammal excreta (heterotrophic nutrition), little is known about how successful the different strategies deployed by carnivorous plants are at obtaining supplemental nutrition. The collection of mammalian faeces by Nepenthes (tropical pitcher plants) is the result of a highly specialized biological mutualism that results in heterotrophic nitrogen gain; however, it remains unknown how effective this strategy is in comparison to Nepenthes species not known to collect mammalian faeces. Methods: We examined how isotopic enrichment varied in the diverse genus Nepenthes, among species producing pitchers for invertebrate capture and species exhibiting mutualisms for the collection of mammal excreta. Enrichment factors were calculated from δ 15 N and δ 13 C values from eight Nepenthes species and naturally occurring hybrids along with co-occurring reference (non-carnivorous) plants from three mountain massifs in Borneo: Mount Kinabalu, Mount Tambuyukon and Mount Trus Madi. Results: All Nepenthes examined, except N. edwardsiana, were significantly enriched in 15 N compared to co-occurring non-carnivorous plants, and 15 N enrichment was more than two-fold higher in species with adaptations for the collection of mammal excreta compared with other Nepenthes. Conclusions: The collection of mammal faeces clearly represents a highly effective strategy for heterotrophic nitrogen gain in Nepenthes . Species with adaptations for capturing mammal excreta occur exclusively at high elevation (i.e. are typically summit-occurring) where previous studies suggest invertebrate prey are less abundant and less frequently captured. As such, we propose this strategy may maximize nutritional return by specializing towards ensuring the collection and retention of few but higher-value N sources in environments where invertebrate prey may be scarce.